HIV-associated disruption of lung cytokine networks is incompletely restored in asymptomatic HIV-infected Malawian adults on antiretroviral therapy. Issue 4 (14th December 2017) - Jambo, Kondwani C.; Tembo, Dumizulu L.; Kamng'ona, Arox W.; Musicha, Patrick; Banda, Dominic H.; Kankwatira, Anstead M.; Malamba, Rose D.; Allain, Theresa J.; Heyderman, Robert S.; Russell, David G.; Mwandumba, Henry C.
The lung is the site most commonly affected by infectious and non-infectious complications of HIV infection [1], even in individuals on effective antiretroviral therapy (ART). HIV infection is associated with lymphocytic alveolitis [2], a condition characterised by the influx of CD8 + T-cells into the alveolar space. This is thought to occur in response to HIV antigens and forms part of the host response to the presence of HIV in the lung [2, 3]. Excessive influx of inflammatory cells in the lung probably leads to tissue damage, disruption of immune cell homeostasis, impaired gas exchange [4] and predisposition to HIV-associated lung complications. Disruption of lung cytokine networks during chronic HIV infection is incompletely restored in individuals on antiretroviral therapy http://ow.ly/klkF30gTtwf